A sedimentary origin for intercrater plains north of the Hellas basin: Implications for climate conditions and erosion rates on early Mars. Issue 11 (14th November 2016) - Salese, Francesco; Ansan, Veronique; Mangold, Nicolas; Carter, John; Ody, Anouck; Poulet, Francois; Ori, Gian Gabriele
Abstract: Understanding the origin (volcanic or sedimentary) and timing of intercrater plains is crucial for deciphering the geological evolution of Mars. We have produced a detailed geological map of the intercrater plains north of the Hellas basin, based on images from the Mars Express High‐Resolution Stereo Camera, the Mars Reconnaissance High‐Resolution Imaging Science Experiment, and Context. Erosional windows and fresh impact craters provide a way of studying the lithology of intercrater plain units. They are composed predominantly of light‐toned sedimentary rocks with subhorizontal bedding over a broad extent (greater than tens of kilometers), showing cross‐bedding stratifications locally. The broad extent, geometry, and flat topography of these sediments favor a formation by aqueous processes (alluvial and lacustrine) rather than airfall (eolian and volcaniclastic). The Late Noachian (~3.7 Ga) sedimentary plains are locally covered by dark‐toned, rough‐textured lava flows of Late Hesperian age (~3.3 Ga). Fe/Mg phyllosilicates were detected within sedimentary rocks, whereas volcanic rocks contain pyroxene and lack signatures of alteration, in agreement with interpretations made from texture and morphology. In erosional windows, the superimposition of sedimentary rocks by younger volcanic flows enables the estimation of an erosion rate of ~1000 nm yr −1 during the Hesperian period (3.3–3.7 Ga). Thus, our study shows that an intense sedimentary cycle occurred on the northern rim of the Hellas basin before and during the Late Noachian, leading to the formation of widespread sedimentary plains, which were then eroded, in agreement with a gradual change in the climatic conditions in this period, and later covered by volcanic flows. Key Points: Intercrater plains on the northern rim of Hellas basin are composed of Noachian sedimentary rocks locally overlain by Hesperian volcanic rocks Sedimentary rocks are composed predominantly of subhorizontal planar layers and fill depressions such as old craters Sedimentary rocks were eroded at a rate of ~1000 nm yr−1 before the volcanic flows emplaced 3.3 Ga ago